A novel TSC1 frameshift mutation c.1550_1551del causes tuberous sclerosis complex by aberrant splicing and nonsense‐mediated mRNA degradation (NMD) simultaneously in a Chinese family. Issue 10 (31st July 2020) - Qiu, Cong; Li, Chengyan; Tong, Xiaoyun; Dai, Luoyang; Liu, Wenda; Xie, Yulie; Zhang, Qimei; Yang, Guohua; Li, Tao
Abstract: Background: Tuberous sclerosis complex (TSC), belongs to autosomal dominant genetic disorder, which affects multiple organ systems in the body, including the skin, brain, lungs, kidneys, liver, and eyes. Mutations in TSC1 or TSC2 was proved to be associated with these conditions. Methods: Gene‐panel Sequence of NGS was used to detect the mutation in a Chinese family. The research further investigates whether aberrant splicing and nonsense‐mediated mRNA degradation (NMD) could serve as a mechanism cause by TSC1 mutation. MINI‐Gene assay apply by pcMINI‐ TSC1 wt/mut plasmids delivered in HeLa and 293T cell lines. Recombinant plasmids expressing wild‐type and mutant‐type EGFP‐ TSC1 were constructed and transiently transfected into human embryonic kidney cells 293T by lipofectamine. Real‐time PCR and Western Blot were performed to analyze the expression of mRNAs and proteins of EGFP‐ TSC1 and NMD factor UPF1. Results: The gene test verified a novel heterozygous TSC1 frameshift mutation ( TSC1 c.1550_1551del) in the proband and her mother. From MINI‐Gene assay, the agarose gel showed that both the mutant and wild‐type mRNA possess two main bands, indicating two splicing modes, named band A and B, respectively. The mutation c.1550_1551del has not produced new splicing site, but there is a selective splicing in varying degree significantly after mutation. On the contrary, function validation assay showed that cells transfected with the mutant TSC1 plasmids expressed significantly lower TSC1 in mRNAs and proteins levels, compared with the wild‐type TSC1 plasmid transfection. A translation inhibitor cycloheximide and small interfering RNA of UPF1 (siRNA‐UPF1) increased mRNA or protein expression of TSC1 significantly in cells transfected with the mutant plasmids. Conclusion: Our study demonstrated that the novel TSC1 frameshift mutation ( TSC1 c.1550_1551del) trigger aberrant splicing and NMD simultaneously, causing decrease of hamartin, then, leading to tuberous sclerosis complex formation. Abstract : This paper verified a novel heterozygous TSC1 frameshift mutation（TSC1 c.1550_1551del）in a Chinese family of tuberous sclerosis complex. MINI‐Gene and function validation assay demonstrated that the novel TSC1 mutation triggered aberrant splicing and NMD simultaneously, caused decrease of hamartin, then resulted in tuberous sclerosis complex.